Drone detection using ultrasonic sensors for passive forward scattering radar system - Abdul Aziz, N.H.; Mahadi, M.A.A.; Mohd Noh, Zarina; Othman, K.A. (2023)
Passive Forward Scattering Radar (PFSR) is a great system that can be used to identify ground moving targets, especially in unsafe areas for reason such as protection and security. Although PFSR can detect any moving target, there are some limitations as PFSR cannot measure height and detect small target such as a drone flying in the sky. A drone is a good device based on the latest technologies, therefore it can also be very dangerous as it can fly in the sky entering prohibited areas that can, for example, breach a border protection system. By developing a system using ultrasonic range sensor interfacing with Raspberry Pi (RPi) and also implementing Internet of Things (IoT) using mobile phone application, which is Telegram, as a security alarm system, this system can integrate with PFSR to be a better system. This project aims to improve the PFSR system with an ultrasonic range sensor remote measuring device. When set up next to the PFSR system, the ultrasonic range sensor has large distance measurement capabilities and use low power to operate. Since ultrasonic range sensors cannot work by themselves, the RPi was used as an operating host that helped to operate and collect data. Then, the data collected was saved into Comma Separated Values (CSV) files to be sent to Telegram mobile application later to the user as notification. The data collected from both systems were compared in order to relate that the ultrasonic range sensor system can indeed support the PFSR system. Since the result was obtained and analysis was done successfully, it can be concluded that the system can support the PFSR system, whereby as the drone height (cm) increased, the signal captured in time (sec) decreased. In addition, this system can contribute in many areas such as borders or streets, to detect speed of vehicles or as a traffic surveillance system and for some other reasons such as protection, security and research.